Inhibition of Human Monoamine Oxidases A and B by Specialized Metabolites Present in Fresh Common Fruits and Vegetables - Claudio Marcello Marzo; Sofia Gambini; Stefania Poletti; Francesca Munari; Michael Assfalg; Flavia Guzzo (Plants, 2022)
Diets rich in fruits and vegetables are associated with better psychological wellbeing and cognitive functions, although it is unclear which molecules and mechanisms are involved. One potential explanation is the inhibition of monoamine oxidases (MAOs), which have been linked to several neurological disorders. The present study investigated the ability of kiwifruit to inhibit MAO-A and MAO-B, refining an in vitro assay to avoid confounding effects. Ultra-performance liquid chromatography/mass spectrometry (UPLC-QTOF) and nuclear magnetic resonance spectroscopy (NMR) were used to select individual kiwifruit metabolites for further analysis. Moreover, extracts of other common fruits and vegetables were screened to identify promising candidate inhibitors. Multiple extracts and compounds inhibited both enzymes, and the selective inhibition of MAO-B by the major kiwifruit specialized metabolite D-(−)-quinic acid was observed. These results suggest that fruits and vegetables contain metabolites that inhibit the activity of MAO-A and -B, offering a potential natural option for the treatment of neurological disorders, in which MAOs are involved.